SQL server 2005 bible - Nielsen, Paul (Wiley, 2007)
Use this comprehensive tutorial and reference to increase productivity and write stored procedures using the language with which you're most familiar. The revised content covers new features such as XML integration, Web services, the .NET Common Language Runtime (CLR), and security updates, making this book a must for any developer or database administrator transitioning to the new version of SQL Server.